De estudante a educadora: uma jornada no ensino de ciências - Steola, Ana Carolina da Silva (Universidade Federal de São Carlos, 2025)
This memorial portrays Ana Carolina da Silva Steola's journey in the field of Science Teaching, from her early discoveries to her establishment as an educator. Her childhood was marked by natural scientific curiosity, nurtured by her family environment and playful school experiences, which led her to develop an investigative perspective on the natural world. In the university environment, her education gained new dimensions through transformative experiences at the Interactive Science Space (EIC) and the Scientific-Cultural Dissemination Center (CDCC). In these spaces, she developed a deep understanding of the importance of making scientific knowledge accessible and meaningful to different audiences. Her participation in initiatives such as the Rondon Project and PIBID further broadened her horizons, allowing her to work in teacher training, develop practical workshops, and establish vital connections between scientific knowledge and community realities. Throughout her journey, she faced and overcame various personal and professional challenges, including periods of grief and health issues, which strengthened her resilience. Contact with the limitations of the educational system and the difficulties faced by students in situations of social vulnerability deepened her conviction about education's transformative role. The memorial evidences a vision of scientific education that transcends the traditional, integrating theory and practice in an inclusive and investigative approach. The author demonstrates how her trajectory was built on the principle that Science teaching must go beyond the classroom limits, promoting significant impact on student formation, professional development of teachers, and community progress. Her narrative emphasizes the importance of constant renewal of pedagogical practices, empathy in the educational process, and commitment to scientific education that dialogues with contemporary social realities.
From student to educator: a journey in science teaching
Keywords: Ensino de ciências; Formação docente; Educação não formal; Memorial acadêmico; Divulgação científica; CIENCIAS HUMANAS::EDUCACAO